Navigating telemedicine for facial trauma during the COVID‐19 pandemic. Issue 4 (9th July 2020) - Said, Mena; Ngo, Victoria; Hwang, Joshua; Hom, David B.
Abstract: Importance: The COVID‐19 pandemic is changing how health care providers practice. As some telemedicine and telecommunication support tools have been incorporated into the otolaryngology practice in response to safety and access demands, it is essential to review how these tools and services can help facilitate facial trauma evaluation during a time when clinical resources are limited. Objective: To review applications of telemedicine for the evaluation of facial trauma to better direct utilization of these methods and technologies during times of limited access to clinical resources such as the COVID‐19 pandemic. Methods: A systematic review was conducted using PubMed, Embase, and Web of Science. Results: After screening 158 titles and abstracts, we identified 16 eligible studies involving facial trauma evaluation using telemedicine. Telemedicine opportunities for facial trauma evaluation have the potential to be developed in the areas of multidisciplinary remote consultations, facial trauma triage, patient engagement, and postoperative follow‐up. Conclusion: The COVID‐19 pandemic is posing obstacles for both providers and patients in the delivery of health care at a time of limited clinical resources. Telemedicine may provide a potential useful tool in the evaluation and triage of facial injuries and patient engagement. Abstract : The COVID‐19 pandemic is posing obstacles for both providers and patients in the delivery of health care at a time of limited clinical resources. Telemedicine may provide a potential tool in the evaluation and triage of facial trauma.